Mediated Religious Literacy: From Digital Escalation to Institutional Closure in the Shalom Aleichem Controversy - Pikri, Zainal; Muthmainnah, Inna (Religió Jurnal Studi Agama-agama, 2025)
This article examines how religious literacy is produced through mediated public discourse by analyzing the controversy surrounding Panji Gumilang and the circulation of Shalom Aleichem (SA) and Havenu Shalom Aleichem (HSA) in Indonesian media. Rather than treating religious literacy as theological knowledge or individual competence, the study conceptualizes it as a mediated achievement shaped by discursive practices in digital and broadcast media. Using qualitative discourse analysis of YouTube content and televised discussions—particularly on TVOne—the article traces how initially ambiguous religious expressions were progressively reclassified through labeling, repetition, and moral framing. Media narratives transformed SA from an interreligious greeting into a marker of religious deviance and geopolitical suspicion, linking it to Judaism, Zionism, and perceived threats to religious and national order. The analysis shows that religious literacy in this context does not emerge through dialogical understanding or theological clarification, but through mediated processes that reduce ambiguity and produce moral certainty. Media actors function as key agents in stabilizing religious meaning by defining what counts as legitimate, deviant, or dangerous religious expression in public space. By foregrounding media discourse as a site of religious meaning-making, this article demonstrates how religious literacy in contemporary Indonesia is shaped through mediation, power, and governance rather than neutral knowledge transmission.